Neuro-Immune Circuits Regulate Immune Responses in Tissues and Organ Homeostasis - Jakob, Manuel O.; Murugan, Shaira; Klose, Christoph S. N. (Frontiers in Immunology, 2020)
The dense innervation of the gastro-intestinal tract with neuronal networks, which are in close proximity to immune cells, implies a pivotal role of neurons in modulating immune functions. Neurons have the ability to directly sense danger signals, adapt immune effector functions and integrate these signals to maintain tissue integrity and host defence strategies. The expression pattern of a large set of immune cells in the intestine charterized by receptors for neurotransmitters and neuropeptides suggest a tight neuronal hierarchical control of immune functions in order to systemically control immune reactions. Compelling evidence suggests that targeting neuronal-immune interactions is a promising strategy to dampen immune responses in autoimmune diseases such as inflammatory bowel diseases or rheumatoid arthritis. In fact, electric stimulation of vagal fibers has been shown to be an extremely effective treatment strategy against overwhelming immune reactions, even after exhausted conventional treatment strategies. Such findings argue that the nervous system is underestimated coordinator of immune reactions and underline the importance of neuro-immune crosstalk for body homeostasis. Herein, we review neuro-immune interactions with a special focus on disease pathogenesis throughout the gastro-intestinal tract.